Evaluating the input and source of faecal contamination in the cattle farming and forested regions of the Oconee watershed. (28th October 2012) - Burt, Christopher; Bachoon, Dave S.
Abstract Sites along Sugar Creek and the Apalachee River were monitored to compare the water quality in cattle farming regions with the forested regions of the Oconee watershed. Dissolved oxygen (6.68 mg/L) and turbidity [23.91 nephelometric turbidity units (NTU)] in Sugar Creek and the Apalachee River were similar. Overall, cattle farming sites along Sugar Creek had higher levels of NO3− and PO4−3 during the summer months. In contrast, the forested sites on the Apalachee River had elevated concentrations of inorganic nutrients only during spring rain events. The concentration of faecal bacteria was greater in the cattle farming areas compared with the level of faecal bacteria in the forested areas, and microbial source tracking with the bovine‐associated Bacteroides (BoBac) DNA marker indicated that cattle were the major source of faecal bacteria in Sugar Creek.